A Critical Evaluation of River Management Models in Malaysia - Chan, Ngai Weng; Ghani, Aminuddin Ab; Roy, Ranjan; Samat, Narimah; Lai, Chee Hui; Tan, Mou Leong (European Publisher, 2019)
Rivers are important natural resources of a country as they provide a wide range of ecosystem services. However, the problem is that rivers in Malaysia are badly degraded due to mismanagement, neglect, pollution and abuse. River management in Malaysia is largely based on the government-centric top-down model which is sectoral-based. This model is ineffective as it has no private sector, NGO and public engagement and support. This paper aims to examine various types of river management models to identify the ones that can be effective in Malaysia. The methodology used a mixture of literature review of existing river management models, secondary data on published journal papers, reports and books on river management. Results of selected river management conferences are also studied, examined and findings synthesized. Primary data is also compiled with selected in-depth qualitative interviews with key government officers, managers of private companies, NGO officers and village heads. Results show that the government (various levels) is traditionally the responsible party in managing rivers, but increasingly, the public, NGOs, businesses and other stakeholders are actively involved. Results also show that holistic river management with active engagement of all stakeholders is necessary. In Malaysia, rivers are found to be intricately intertwined with all aspects of development. It was concluded that the Public-Private Partnership (PPP) model is an effective river management model in Malaysia as it conserves the river and its environment, and brings together all parties for building their capacities in river management towards achieving many Sustainable Development Goals (SDGs).